Blocking TNF-α in Complex Regional Pain Syndrome Type I: A Case of Reflex Sympathetic Dystrophy Resolved with Etanercept in a Patient with Ankylosing Spondylitis - Ahmet ÖZGÜL,; Dilek VURAL,; Mehmet Ali TAŞKAYNATAN, (Archives of Rheumatology, 2011)
Complex regional pain syndrome type I (CRPS1) is a painful clinical condition that may develop mostly as a result of trauma affecting the limbs. Hyperalgesia, allodynia, spontaneous pain, and autonomic disturbances along with swelling and impairment of motor functions are the hallmarks. Ultimately, this syndrome may lead to disability. Although many different kinds of treatments have been tried, the success of these treatments has been limited. Inflammatory signs appear especially in the early and mid-stages of the disease. These findings may favor the use of new treatment modalities including the use of new generation medicines like monoclonal antibodies in the treatment of CRPS. In this article, we report the complete resolution of CRPS1 with the TNF-a-blocker etanercept in a 62-year-old female patient with ankylosing spondylitis.